Enhanced Tau Protein Translation by Hyper-Excitation - Kobayashi, Shunsuke; Tanaka, Toru; Soeda, Yoshiyuki; Takashima, Akihiko (Frontiers in Aging Neuroscience, 2019)
Tau is a microtubule-associated protein, localizing mainly in the axon of mature neurons. Phenotypic analysis of Tau knockout mice has revealed an impairment of synaptic plasticity but without gross changes in brain morphology. Since we previously described the presence of tau mRNA in the somatodendritic compartment, including the postsynapse, and demonstrated that it could be locally translated in response to glutamate, it appears that the regulated translation of synaptic tau can have a direct impact on synaptic function. Using SH-SY5Y cells, we herein confirm that glutamate dose-dependently regulates the translation of tau protein without altering tau mRNA levels. This is supported by the finding that cycloheximide blocks glutamate-stimulated increases in tau protein levels. Our observation that that neural excitation can directly upregulate tau mRNA translation helps explain the pathological accumulation of tau in the somatodendrite.